Antibacterial activity of docynia fruit extract against antib iotic resist ant bacterium causing upper respiratory tr act infectio n (m o r ax el I a c at arrlt al i s) - Thư, Nguyễn Thị Minh; Anh, Nguyễn Thị Phương; Hà, Bùi Thị Việt (VNU Journal of Science: Natural Sciences and Technology; Vol 29 No 2, 2013)
Abstract.